2007
DOI: 10.1289/ehp.10446
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–Fetal Transfer of Domoic Acid in Rats at Two Gestational Time Points

Abstract: Background and objectivesPrenatal exposure to asymptomatic doses of domoic acid (DA) causes learning and memory deficits later in life; therefore, we sought to measure distribution of DA in maternal plasma and brain, prenatal brain, and amniotic fluid 1 hr after exposure, a time frame that normally encompasses acute seizure behavior.MethodsPregnant rats were given a single intravenous dose of DA (0.6 or 1.6 mg/kg body weight) at either gestational day (GD) 13 or GD20, which correspond to the beginning of rat e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…These animals experienced much higher toxin levels than those estimated herein for E. glacialis. However, DA is actually cleared rapidly in adults but not cleared effectively from the fetal unit (Maucher & Ramsdell 2007), and the fetus is thus considered to be more susceptible to DA poisoning on the basis of exposure during pregnancy. In fact, fetal poisoning was proposed by Ramsdell & Zabka (2008) to have a more prominent effect later in life, manifest as a greater likelihood of developing neurological disease.…”
Section: Da In Right Whalesmentioning
confidence: 99%
“…These animals experienced much higher toxin levels than those estimated herein for E. glacialis. However, DA is actually cleared rapidly in adults but not cleared effectively from the fetal unit (Maucher & Ramsdell 2007), and the fetus is thus considered to be more susceptible to DA poisoning on the basis of exposure during pregnancy. In fact, fetal poisoning was proposed by Ramsdell & Zabka (2008) to have a more prominent effect later in life, manifest as a greater likelihood of developing neurological disease.…”
Section: Da In Right Whalesmentioning
confidence: 99%
“…Prenatal exposure of xenobiotic chemicals that interfere with the glutamate recep--ture of the brain which should lead to anomaly of higher brain function that is different from acute neurotoxicity known for such chemicals to induce in adults (Bondy and Campbell, 2005). A marine biotoxin domoic acid (DA) which is structurally related to glutamate, and activates -pionic acid (AMPA) and kinate subtypes of glutamate receptors (Pulido, 2008) is known to cause acute symp-1990), and DA induced acute neurotoxicity in animal Intrauterine environment-genome interaction and Children's development (2): Brain structure impairment and behavioral disturbance induced in male mice offspring by a single intraperitoneal administration of domoic acid (DA) to their dams model (Chandrasekaran et al is also known to cross the placenta, and enters prenatal brain tissue in rats (Maucher and Ramsdell, 2007). Therefore, prenatal exposure of DA may disrupt the neural activities by excessive stimulation of glutamate recep--a transient transplacental DA exposure in utero induced alteration of the neurobehavioral parameters and correin their adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, experiments with rats have demonstrated that low DA doses can precondition the brain and induce tolerance against higher DA doses in young, but not aged, rats (Kerr et al 2002, Hesp et al 2004. In humans, the most susceptible individuals to low DA doses may include pregnant and nursing women, since experiments with rats showed that (1) low DA doses may be transferred through milk and placenta, and accumulated in the amniotic fluid of pregnant rats and the brain of prenatal rats (Maucher & Ramsdell 2005, 2007; and (2) DA can reach the brain without restriction, causing neurological and behavior effects later in the life for prenatal rats (Dakshinamurti et al 1993, Levin et al 2005, Maucher & Ramsdell 2007. In humans, the elderly (> 65 yr) are most susceptible, since DA is cleared from the plasma through the kidneys (Suzuki & Hierlihy 1993), and old individuals are thought to have reduced ability to eliminate DA through the renal system (Xi et al 1997, Pulido 2008.…”
Section: Discussionmentioning
confidence: 99%